Probing Corticospinal Control During Different Locomotor Tasks Using Detailed Time-Frequency Analysis of Electromyograms - Filli, Linard; Meyer, Christian; Killeen, Tim; Lörincz, Lilla; Göpfert, Beat; Linnebank, Michael; von Tscharner, Vinzenz; Curt, Armin; Bolliger, Marc; Zörner, Björn (Frontiers in Neurology, 2019)
Locomotion relies on the fine-tuned coordination of different muscles which are controlled by particular neural circuits. Depending on the attendant conditions, walking patterns must be modified to optimally meet the demands of the task. Assessing neuromuscular control during dynamic conditions is methodologically highly challenging and prone to artifacts. We investigated changes in neuromuscular control during various locomotor tasks. Activity in tibialis anterior (TA) and gastrocnemius medialis (GM) muscles was monitored by surface electromyography (EMG) in 27 healthy volunteers (11 female) during regular walking, walking while engaged in simultaneous cognitive dual tasks, walking with partial visual restriction and skilled, targeted locomotion. Whereas EMG intensity of the TA and GM was considerably altered while walking with partial visual restriction and during targeted locomotion, dual-task walking induced only minor changes in total EMG intensity compared to regular walking. Targeted walking resulted in enhanced EMG intensity of GM in the frequency range associated with Piper rhythm synchronies. Likewise, targeted walking induced enhanced EMG intensity of TA at the Piper rhythm frequency around heelstrike, but not during the swing phase. Our findings indicate task- and phase-dependent modulations of neuromuscular control in distal leg muscles. Enhanced EMG intensity at the frequency of the Piper rhythm during targeted walking points towards enforced corticospinal drive during challenging locomotor tasks. These findings indicate that comprehensive time-frequency EMG analysis is able to gauge cortical involvement during different movement programs and might be used to monitor corticospinal integrity during neurorehabilitation interventions.